Gag-specific CD4+ T-cell responses are associated with virological control of paediatric HIV-1 infection - Prendergast, A; Goodliffe, H; Clapson, M; Cross, R; Tudor-Williams, G; Riddell, A; Daniels, J; Williams, A; Goulder, P (Lippincott, Williams and Wilkins, 2011)
HIV-specific Elispot responses were investigated in 57 antiretroviral therapy-naïve children, of median age 9.9 years. CD8+ T-cell responses were detected in 96% children; Nef was the immunodominant protein. Responses broadened over time but there was no association between magnitude, breadth or specificity of response and viraemia. Gag-specific CD4+ T-cell responses, detectable in 26% children, correlated inversely with viraemia (R = -0.43, P < 0.001), suggesting that preservation of this cell population may be an important goal of therapeutic/vaccine strategies.